Modelo de desarrollo organizacional hotelero para crear estrategias de desarrollo local en la hostería Rumipamba de las Rosas - Jiménez Trujillo, Andrea Vanessa (2020)
The thesis project was developed in order to elaborate a hotel organizational model that promotes community tourism and to link it in the Patain community. Salcedo canton located in the Cotopaxi province, since it is not a well known place, for this reason it needs to elaborate a local development strategy that promotes community tourism by identifying tourist attractions, The information was gathered from different texts, web pages, information from the GAD parish and the MINTUR collaboration.